Commentary on "Measuring Aksak Rhythm and Synchronization in Transylvanian Village Music by Using Motion Capture" - Jerome Cler (Empirical Musicology Review, 2016)
While the methodologies employed by Bonini-Baraldi et al., document the rhythms produced in a single set of performances, those methodologies would be more relevant if applied to a comparative study of various aksak rhythms, rather than to a study of a single rhythmic pattern. The results of the present study are not very different from the findings of R.I.T.M.O seminar (J. During, J. Cler. et al,) during the mid 1990s.